Volatility And The Natural Resource Curse. - Ploeg, F; Poelhekke, S (OxCarre, 2008)
We provide cross-country evidence that rejects the traditional interpretation of the natural resource curse. First, growth depends negatively on volatility of unanticipated output growth independent of initial income, investment, human capital, trade openness, natural resource dependence and population growth. Second, the direct positive effect of resources on growth is swamped by the indirect negative effect through volatility. Third, with well developed financial sectors, the resource curse is less pronounced. Fourth, landlocked countries with ethnic tensions have higher volatility and lower growth. Fifth, restrictions on the current account raise volatility and depress growth whereas capital account restrictions lower volatility and boost growth. Our key message is thus that volatility is a quintessential feature of the resource curse.